PERCEPTION AND READINESS TO ADOPT ARTIFICIAL INTELLIGENCE IN DENTISTRY AMONG NEWLY GRADUATED DENTISTS IN HO CHI MINH CITY, VIETNAM, IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the knowledge, attitudes, and readiness to adopt artificial intelligence applications in dental practice among newly graduated dentists in Ho Chi Minh city, Vietnam, in 2025.Subjects and methods: A descriptive cross-sectional study was conducted from March to September 2025 on 164 newly graduated dentists selected by convenience sampling. Data were collected through a structured online questionnaire and analyzed using SPSS 26.0 software with descriptive statistics, Chi-square, Mann-Whitney U, and Kruskal-Wallis tests (p < 0.05).Results: Most participants (94.5%) had heard of artificial intelligence in healthcare and 72% were aware of its application in dentistry. Although 98.7% expressed interest in using artificial intelligence, only 36% trusted its diagnostic accuracy. Higher technological proficiency and participation in artificial intelligence-related training were significantly associated with greater willingness to adopt artificial intelligence (p < 0.05). Diagnostic imaging, implantology, and prosthodontics were rated as the most promising fields, while lack of training (79.3%) and implementation costs (65.9%) were the main barriers.Conclusion: Newly graduated dentists show positive attitudes toward artificial intelligence but limited confidence in its diagnostic capability. Structured education and interdisciplinary collaboration are essential to enhance competence and readiness for artificial intelligence integration in dental practice.
Keywords: Artificial intelligence, dentistry, perception, attitude, technology adoption, dental education.